THE DEVELOPMENT OF STUDENT LEADERSHIP WITHIN THE PROTOKOLER BUMI SILIWANGI ORGANIZATION IN INDONESIA UNIVERSITY OF EDUCATION - Cecep Darmawan, Rizal Wirahadikusumah Idrus Affandi (Department of Civic Education, 2016)
This research is motivated by the phenomenon of student organization that is related in the protocol in Protokoler Bumi Siliwangi UPI organization develop student leadership attitude. This research approach is qualitative descriptive method, to get the real and factual descriptian. Data collection techniques in this study were interviews, observation, literature study, study documentation and triangulation. The research found that 1) a curriculum Protokoler Bumi Siliwangi UPI organization referred to the rules of life (perdub), which governs the education and training (training); 2) the main of activity in the Protokoler Bumi Siliwangi UPI organization are divided into two: internal and external. Internal activities are activities of realization of the program of work, while the external activity is Keprotokoleran service activities; 3) methods used in developing the leadership style of leadership is democracy collaborated with authorit, and the responsibilities are distributed, and 4) the constraints faced by Protokoler Bumi Siliwangi organization UPI in developing attitude student leadership are contraints of personal and technical in field.Keywords: The Student Organization, Character, Leadership